Model latihan fisik jalan kaki dengan pemberian jus galoba terhadap komposisi lemak tubuh dan status antioksidan pada wanita usia >55 tahun - Abdul Rivai Saleh Dunggio (AcTion: Aceh Nutrition Journal, 2021)
Walking can affect the muscles to stretch which can improve physical fitness for prevention in elderly women. Galoba contains flavonoids that have anti-oxidative properties and play a role in preventing damage to cells and their cellular components by reactive free radicals. The aim of the study was to determine the effectiveness of the physical exercise model walking by giving galoba juice on body fat composition and antioxidant status in women aged > 55 years. This study was a true experiment with a pre-posttest with a control group. Consecutive admission sampling technique, as many as 20 people. Data collection was carried out by observing mothers who did walking sports by giving galoba juice for 14 consecutive days with a walking time of 25 minutes. Statistical was using the Independent t-test. The results obtained that the average value of body fat composition after walking was 38,1% <after walking with galoba juice 42,2%, p= 0,372 (p > 0,05). The average value of total anti-oxidants after walking was 1,58 µg/mL <after walking with galoba juice was 1,59 µg/mL, p= 0,527 (p > 0,05). The conclusion is that there is no effect of walking physical exercise on body fat composition and there is no effect of the physical exercise model walking with the provision of galoba juice on total antioxidant levels.